The cancer atlas - Mackay, Judith (American Cancer Society, 2006)
This atlas illustrates the latest available data on the cancer epidemic, showing causes, stages of development, and prevalence rates of different types of cancers by gender, income group, and region. It also examines the cost of the disease, both in terms of health care and commercial interests, and the steps being taken to curb the epidemic, from research and screening to cancer management programs and health education.
Keywords: nádory; onkologie; Neoplasms